A note on the rooting of shorea acuminata and shorea parvifolia leafy stem cuttings - Ab Shukor, Nor Aini; Ling, Tiing Tchin (Forest Research Institute Malaysia, 1993)
Half-leaf 2-node stem cuttings of 3 types (terminal, middle and basal) were taken from 18-month-old potted seedlings of Shorea acuminata and S. parvifolia and given 6 hormonal treatments (0, 75, 100, 125 and 150 µg IBA, and 100 µg IBA + 100 µg NAA) before planting in 2 types of rooting media (coconut fibre and paddy husk). They were kept moist by spraying with an automatic mist sprinkler (60% relative humidity) and maintained at 25°C under 12-h photoperiods (irradiance 27 W/m²). Over 80 and 65% of the cuttings survived and rooted in S. parvifolia and S. acuminata, respectively. Terminal cuttings survived best and basal cuttings least. The best hormone treatments were 100 µg IBA for S. acuminata in coconut fibre and 150 µg IBA for S. parvifolia in paddy husk. Root development was superior in S. parvifolia, and coconut fibre was the best medium for root development.